Weberian Digital Bureaucracy in the Placement of Indonesian Migrant Workers: Policy Analysis of the Special Placement Program to Taiwan (SP2T) - Lonita, Theresia Evy (Eduvest - Journal of Universal Studies, 2025)
The Special Placement Program to Taiwan (SP2T) is an innovative initiative aimed at streamlining the placement of Indonesian Migrant Workers (PMI) to Taiwan by eliminating placement costs through digitization, bypassing the Indonesian Migrant Worker Placement Company (P3MI). This study analyzes the principles of Digital Weberian Bureaucracy (DWB) such as intelligent efficiency, sizing-ip objectivity, and remote rationality in the implementation of SP2T, utilizing the Indonesian Migrant Worker Protection Computerized System (SISKOP2MI). The research focuses on how digitization can address issues like overcharging in worker placement. The study used qualitative methods, including interviews with 15 SP2T candidates from the first batch in 2025, representatives of stakeholders, and document studies of regulations and reports related to SP2T. The findings highlight that DWB’s goals of efficiency and objectivity can be achieved with human resource transformation, innovation in technology use, and overcoming system errors. The implementation of SP2T has been successful, reducing placement costs and speeding up the process compared to P3MI; however, collaboration among companies, HSDC Taiwan, and KDEI is still weak in creating a consistent placement quota. The study recommends promoting SP2T proactively to Taiwanese companies and improving coordination with training centers and vocational schools to increase labor supply. Furthermore, facilitating Chinese language training for migrant workers by BP2MI before departure can better prepare them for working in Taiwan.